ADVANTAGES OF PREOPERATIVE CONSULTATION IN THE REHABILITATION OF THE PERSON SUBMITTED HIP ARTHROPLASTY: AN INTEGRATED LITERATURE REVIEW - Bruno Miguel Vivas Pina; Cristina Lavareda Baixinho (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Introduction: Hip arthroplasty is a frequent surgery that, combined with pain and decreased mobility, increases dependence on self-care and is a predictor of loss of functionality. Objective: To determine the advantages of preoperative preparation consultation in the evolution of postoperative functionality of the person undergoing hip artroplasty. Method: Integrative Literature Review, eligibility criteria were defined for the bibliographic sample. Results: The bibliographic sample consisted of 16 articles that allow us to respond to the research objective. Structured recovery programs with preoperative consultation reduce postoperative complications and average length of stay, promote better pain management and faster recovery through an interprofessional approach. Conclusions: The rehabilitation program should start in the preoperative phase because increased knowledge about surgery, rehabilitation program and transition to the community translates into health, social and economic gains.